2007
DOI: 10.1152/ajpregu.00858.2006
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin effects on inflammation and performance recovery following eccentric exercise-induced muscle damage

Abstract: Downhill running is associated with fiber damage, inflammation, delayed-onset muscle soreness, and various functional deficits. Curcumin, a constituent of the Indian spice turmeric has been investigated for its anti-inflammatory activity and may offset some of the damage and functional deficits associated with downhill running. This study examined the effects of curcumin on inflammation and recovery of running performance following downhill running in mice. Male mice were assigned to downhill placebo (Down-Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
188
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(205 citation statements)
references
References 43 publications
9
188
0
8
Order By: Relevance
“…Several studies have confirmed that curcumin blocks the activity of transcription factor NF-kappaB, reduces AP-1 binding to DNA and causes decreased production of COX-2, all of which play a role in inflammation (22,34,35). Curcumin appears to target NF-kappaB as opposed to COX-2, indicating the potential for less serious side effects than NSAIDs (22). This mechanism could also be responsible for reduced inflammatory response to exercise observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that curcumin blocks the activity of transcription factor NF-kappaB, reduces AP-1 binding to DNA and causes decreased production of COX-2, all of which play a role in inflammation (22,34,35). Curcumin appears to target NF-kappaB as opposed to COX-2, indicating the potential for less serious side effects than NSAIDs (22). This mechanism could also be responsible for reduced inflammatory response to exercise observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have evaluated for the effect of curcumin on DOMS (21)(22)(23)(24). However, to the best of our knowledge, no study to date has tested administration of 150mg curcumin supplement immediately after intensive eccentric exercise.…”
Section: Nakhostinmentioning
confidence: 99%
“…The majority of studies that have been conducted in an attempt to reduce EIMD have focused on taking medicines, using massage, antioxidants supplementation and using other potential agents (Peake et al 2005b;Hilbert et al 2003;Lu et al 2006;Davis et al 2007;Savage and Clarkson 2002). However, the results of these studies varied greatly, and more studies of new treatments for reducing EIMD are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has anti-inflammatory, 1,2) free radical scavenger-mediated antioxidant, 3,4) anticancer, 5,6) anti-allergy, 7,8) anti-arthritis, 9,10) anti-diabetes, 11) hepatoprotective, 12) neuroprotective, 13) antidepressant, 14) and muscle damage protective 15) physiological effects. With regard to chronic inflammation that is particularly associated with lifestyle-related diseases, many recent studies have investigated the inhibitory effects of curcumin on activated nuclear factor-kappaB (NF-κB), 16,17) and signal transducer and activator of transcription 3 (STAT3).…”
mentioning
confidence: 99%